Contact urticaria syndrome with IgE antibody against a cefotiam‐unique structure, evoked by nonapparent exposure to cefotiam. (22nd May 2017) - Takahagi, S.; Tanaka, A.; Iwamoto, K.; Ishii, K.; Hide, M.
Summary: A 26‐year‐old woman presented with recurrent attacks of widespread urticaria and systemic symptoms. The patient was a nurse, and the attacks occurred only in her workplace, without an apparent trigger. A patch test to cefotiam (CTM) induced an immediate skin reaction. ELISA detected the patient's serum IgE antibody binding to CTM conjugated with human serum albumin (CTM‐HSA), and her basophils released histamine in response to CTM‐HSA in a histamine release assay (HRA). Both reactions in ELISA and HRA were inhibited by pretreatment of the patient's serum or basophils with cefotiam. No crossreactivity in skin tests or in vitro assays was observed against other antibiotics, even those containing a beta‐lactam ring and/or side chains similar to CTM. Certain antibiotics including CTM may cause extremely sensitive and specific contact urticaria syndrome, which is mediated by IgE and evoked even without apparent skin contact with the culprit drug and in the absence of any history of an allergic reaction against other antibiotics with similar structures.